THE RESEARCH KNOWLEDGE MANAGEMENT AND INTERDISCIPLINARY INNOVATION IN THE DESIGN AND DEVELOPMENT OF PRODUCT, PACKAGING AND STORES TO PROMOTE AND DEVELOP TOURISM CAREER IN THE COMMUNITY OF KLONG SUAN 100 YEARS MARKET ACCORDING TO THE SUFFICIENCY ECONOMY PHILOSOPHY. - Kamonnarakitraksa, Thathana; Siripithakul, Arnut; Phontharaphong, Yuvadee; Ananwettayanon, Chukiat (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2023)
This applied research was to transfer knowledge and design innovation and develop products, packaging, and architecture, in addition to promoting and developing tourism careers. The area for this research was the community of Klong Suan 100 Years Market, Moo 1, Klong Suan sub-district, Bang Bo district, Samut Prakan province. Research instruments were a survey of the area, an interview, a questionnaire, and operation training. Samples were 50 people—vendors and people who live in the community of Klong Suan 100 Years Market. Data collection included physical data, economic and social data, as well as the area's identity. Then use the data to analyze, design, and develop products, packaging, and kiosks for selling products, including store layout and storefront layout, to create a prototype suitable for the community. Bring productivity and practical knowledge to the community by organizing 5 workshop projects. Then evaluate the product and the 5 training programs of the participants in order to further expand the results. The result of the training on transferring knowledge in all 5 courses found that the productivity was a model souvenir product to promote tourism, packaging formats that create a promotional identity, a format for organizing stores that promote sales that are consistent with the way of life and cultural identity of the old market community, kiosk format for selling products that create an identity for the market and creating an online store increase sale channel. The results of the evaluation of the 5 training programs, separated into various aspects, which include the design and development of prototypes, the activities of organizing training projects, the transfer of knowledge to the community, and the transfer of theoretical knowledge via online, it was found that the level of satisfaction was the highest for all 5 courses. After conducting the research project, the researcher prepared a knowledge manual for all 5 courses to be able to transfer and expand the results to other community areas of interest.